Outcomes of early catheter ablation for ventricular tachycardia in adult patients with structural heart disease and implantable cardioverter-defibrillator: An updated systematic review and meta-analysis of randomized trials - Shalganov, Tchavdar; Stoyanov, Milko; Traykov, Vassil (Frontiers in Cardiovascular Medicine, 2022)
Abstract. Aims: Catheter ablation (CA) for ventricular tachycardia (VT) can improve outcomes in patients with ischemic cardiomyopathy. Data on patients with non-ischemic cardiomyopathy are scarce. The purpose of this systematic review and meta-analysis is to compare early CA for VT to deferred or no ablation in patients with ischemic or non-ischemic cardiomyopathy. Methods and results: Studies were selected according to the following PICOS criteria: patients with structural heart disease and an ICD for VT, regardless of the antiarrhythmic drug treatment; intervention – early CA; comparison – no or deferred CA; outcomes – any appropriate ICD therapy, appropriate ICD shocks, all-cause mortality, VT storm, cardiovascular mortality, cardiovascular hospitalizations, complications, quality of life; published randomized trials with follow-up at least 12 months. Random-effect meta-analysis was performed. Outcomes were assessed using pooled study-level data and reported as odds ratio (OR) or mean difference with 95% confidence intervals (CI). Stratification by left ventricular ejection fraction (LVEF) was also done. Eight trials (n=1076) met the criteria. Early ablation was associated with reduced incidence of ICD therapy (OR 0.53, 95%CI 0.33-0.83, p=0.005) and shocks (0.52, 95%CI 0.35-0.77, p=0.001), VT storm (OR 0.58, 95%CI 0.39-0.85, p=0.006), and cardiovascular hospitalizations (OR 0.67, 95%CI 0.49-0.92, p=0.01). All-cause and cardiovascular mortality, complications, and quality of life were not different. Stratification by LVEF showed reduction of ICD therapy only with higher EF (high EF OR 0.40, 95% CI 0.20-0.80, p=0.01 vs low EF OR 0.62, 95% CI 0.34-1.12, p=0.11), while ICD shocks (high EF OR 0.54, 95% CI 0.25-1.15, p=0.11 vs low EF OR 0.50, 95% CI 0.30-0.83, p=0.008) and hospitalizations (high EF OR 0.95, 95% CI 0.58-1.58, p=0.85 vs low EF OR 0.58, 95% CI 0.40-0.82, p=0.002) were reduced only in patients with lower EF. Conclusion: Early CA for VT in patients with structural heart disease is associated with reduced incidence of ICD therapy and shocks, VT storm and hospitalization. There is no impact on mortality, complications, and quality of life. (The review protocol was registered with INPLASY on June 19, 2022, #202260080).